Bacterial contamination of fabric and metal-bead identity card lanyards: A cross-sectional study - Thomas Pepper; Georgina Hicks; Stephen Glass; John Philpott-Howard (Elsevier, 2014)
Summary: In healthcare, fabric or metal-bead lanyards are universally used for carrying identity cards. However there is little information on microbial contamination with potential pathogens that may readily re-contaminate disinfected hands. We examined 108 lanyards from hospital staff. Most grew skin flora but 7/108 (6%) had potentially pathogenic bacteria: four grew methicillin-susceptible Staphylococcus aureus, and four grew probable fecal flora: 3 Clostridium perfringens and 1 Clostridium bifermentans (one lanyard grew both S. aureus and C. bifermentans). Unused (control) lanyards had little or no such contamination. The median duration of lanyard wear was 12 months (interquartile range 3-36 months). 17/108 (16%) of the lanyards had reportedly undergone decontamination including wiping with alcohol, chlorhexidine or chlorine dioxide; and washing with soap and water or by washing machine. Metal-bead lanyards had significantly lower median bacterial counts than those from fabric lanyards (1 vs. 4 CFU/cm2; Mann-Whitney U = 300.5; P < 0.001). 12/32 (38%) of the metal-bead lanyards grew no bacteria, compared with 2/76 (3%) of fabric lanyards. We recommend that an effective decontamination regimen be instituted by those who use fabric lanyards, or that fabric lanyards be discarded altogether in preference for metal-bead lanyards or clip-on identity cards. Keywords: Lanyard, Contamination, Identity card, Metal, Fabric